Antioxidant activity and DNA damage protection by lycopene from fresh and cooked tomato - Juthaluk Wongchaichana; Rakshit, Sudip Kumar; Athapol Noomhorm; Ranamukhaarachchi, S.L.; RTG Fellowship (Pathum Thani,Thailand : Asian Institute of Technology, 2008)
The major natural carotenoid in tomato is lycopene. The varieties and cooking method effects on lycopene content and its antioxidant activity was studied. The varieties that were used in this experiment were Plum tomato, Beef tomato, Cherry tomato, Seeda tomato and Red honey tomato. Plum tomato had the highest lycopene content that was 73.022 mg/kg while Beef tomato had the lowest lycopene content that was 31.970 mg/kg. Total lycopene content from different varieties of tomato was significant difference, excepted Seeda tomato and Red Honey tomato which were not difference. In addition, Plum tomato also had the highest antioxidant activity and Beef tomato had the lowest antioxidant activity. % DPPH Scavenging of Plum tomato was 88.744% and Beef tomato was 87.817%.% DPPH Scavenging of all varieties was not difference, excepted Plum tomato that was different from Cherry tomato and Beef tomato. A commercial tomato sauce sample was found to have less lycopene content and antioxidant activity than fresh tomato and concentrated tomato slurry. Hence, processing and other ingredients have an effect on lycopene content. The effect of boiling, baking, microwave and frying on lycopene content analysis and DPPH antioxidant activity was different. Boiling and baking seem to increase content and antioxidant activity. On microwave heating, the lycopene content increased and they deceased on longer exposed. The microwave seemed to have an effect on antioxidant activity on prolong exposure. On the other hand, frying in palm oil led to increase lycopene content but decease in antioxidant activity. It is concluded that as the content and activity results are not following the same trends. A better method of measuring antioxidant activity needs to be studied. The protection that lycopene is capable of could not be demonstrated on the plasmid DNA due to a problem with the sample DNA
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Lycopene; Tomatoes; DNA damage